India’s New Education Policy in 2020: Antinomies of Progress - Divyarajsinh Vanar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
This paper contains a comprehensive analysis of the New Education Policy of India (2020). For instance, it would be interesting to analyse, compare and understand whether the BJP-ruled Indian government passed the National Educational Policy (NEP; 2020) so as further privatize the nation’s educational system. What multidimensional impacts could the New Education Policy (NEP) have on the future of India’s educational system? We would also like to investigate how it affects institutional autonomy, premier public universities, cultural dynamics, and intellectual diversity. This paper investigates how the NEP will reshape education in India. The broad conclusion is that said education is witnessing deep shifts and changes which will not only lead to a deepening of social inequalities and affect learning but will also burden poor and middle-class families with added financial pressure.